Distributed-memory computing with the Langley Aerothermodynamic Upwind Relaxation Algorithm (LAURA) - Riley, Christopher J.; Cheatwood, F.McNeil (Advances in engineering software (1992), 1998)
The Langley Aerothermodynamic Upwind Relaxation Algorithm (LAURA), a Navier–Stokes solver, has been modified for use in a parallel, distributed-memory environment using the Message-Passing Interface (MPI) standard. A standard domain decomposition strategy is used in which the computational domain is divided into subdomains with each subdomain assigned to a processor. Performance is examined on dedicated parallel machines and a network of desktop workstations. The effect of domain decomposition and frequency of boundary updates on performance and convergence is also examined for several realistic configurations and conditions typical of large-scale computational fluid dynamic analysis.